Textbook Evaluation: Teaching Grammar - Krátká, Valerie (Univerzita Pardubice, 2012)
The thesis concentrates on evaluation of textbooks in terms of grammar. The outcome of the theoretical part is the criteria for textbook evaluation and choice in terms of grammar requirements. Practical part then focuses on evaluation and comparison of two textbooks on the basis of criteria which are given in the theoretical part. The aim is to find out if the textbooks used nowadays somehow match the appropriate criteria concerning grammar practising and presentation.
Hodnocení učebnic: Výuka gramatiky
Keywords: material didactic aids; textbooks; grammar; communicative competence; criteria and evaluation; materiální didaktické pomůcky; učebnice; gramatika; komunikativní kompetence; kritéria a hodnocení